Non-alcoholic fatty liver disease related knowledge among a sample of Egyptians: an exploratory cross-sectional study - Mona A. Hegazy; Arwa Elshafei; Arwa Elshafei; Marwa Rashad Salem; Omar Ashoush; Ahmed Abdelghani (Frontiers Media S.A., 2024)
IntroductionThe global prevalence of Non-alcoholic fatty liver disease (NAFLD) is about 25% worldwide making it an actual health disaster. This study aimed to assess non-alcoholic fatty liver disease (NAFLD)-related knowledge in a sample of Egyptians.Materials and methodsThis exploratory cross-sectional study was conducted on 3,124 individuals using 2000 online and 1,124 printed questionnaire forms. These questionnaires, covering sociodemographic characteristics and fatty liver-related knowledge, comprised 30 items. These items include ten questions on definition, symptoms, and complications: 14 about risk factors, and six about prevention and therapy. The data were analyzed using SPSS. Categorical variables were expressed in proportions and percentages. Chi-square and Fisher's exact tests were applied as appropriate. For quantitative variables, the t-test, Mann-Whitney U test, Kruskal-Wallis test, and ANOVA test were used for comparisons.ResultsA total of 3,124 respondents were enrolled in the current study. More than half (57%) were females, and 25% ranged in age from 18 to 29. 10.8% of the participants believed that fatty liver patients were asymptomatic, and 34% knew that fatty liver disease was caused by fat accumulation. Regarding predisposing factors, hypercholesterolemia, increased fat in the diet, and obesity had the highest proportion of accurate responses (60, 54, and 46.6%, respectively). On the other hand, 89.3% believed it could be prevented, and 81.4% of the respondents knew that weight reduction could prevent the condition. All respondents (100%) stated wrongly that it was a familial disease related to aging, and most participants (97.3%) did not believe that fatty liver could be treated. Females demonstrated a significantly higher score in preventive measures, while the employed participants scored significantly higher in general knowledge of fatty liver, risk factors, and preventive measures.ConclusionDespite the increasing NAFLD prevalence, the current study indicated that Egyptians had fair to moderate knowledge about fatty liver and its risk factors, preventive measures, and therapy. However, a false belief was documented by all respondents that it is a disease that runs in families and occurs only in old age. A fundamental shift in healthcare management with a prioritization of prevention, proactive measures, and early detection of NAFLD should be emphasized.